2016
DOI: 10.3329/jbcps.v33i3.28063
|View full text |Cite
|
Sign up to set email alerts
|

Medication Bezoar Causing acute Gastric Outlet Obstruction: A Case Report

Abstract: Acute gastric outlet obstruction is relatively uncommon and mostly due to foreign bodies related to food impaction, with meat being the most frequent culprit. The diagnostic approach to acute gastric outlet obstruction is similar to other cause of GOO. However, therapeutic options differ for each patient. The diagnosis should be made in prompt time to prevent life threatening complications due obstruction and/or effect of medication forming bezoar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Because of the advancement of technology and time delivery-facilitated drug tablets/capsules to be slowly dissolved and gradually release active ingredients of the medication, extended-release medicines, e.g., nifedipine and verapamil, are coated with cellulose acetate; cellulose acetate may amass and lead to the progression of gastric bezoar [6]. Moreover, aluminum hydroxide gel, enteric-coated aspirin, sucralfate, cholestyramine, enteral feeding formulas, mesalamine pills, and meprobamate appear to contribute to the development of pharmacobezoars [47, 48]. Furthermore, a case by Croitoru et al [10] reported a sodium polystyrene sulfonate gastric bezoar in a patient who mechanically ventilated after cardiopulmonary resuscitation secondary to pericarditis, primary lung cancer, and kidney failure with concomitant hyperkalemia.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Because of the advancement of technology and time delivery-facilitated drug tablets/capsules to be slowly dissolved and gradually release active ingredients of the medication, extended-release medicines, e.g., nifedipine and verapamil, are coated with cellulose acetate; cellulose acetate may amass and lead to the progression of gastric bezoar [6]. Moreover, aluminum hydroxide gel, enteric-coated aspirin, sucralfate, cholestyramine, enteral feeding formulas, mesalamine pills, and meprobamate appear to contribute to the development of pharmacobezoars [47, 48]. Furthermore, a case by Croitoru et al [10] reported a sodium polystyrene sulfonate gastric bezoar in a patient who mechanically ventilated after cardiopulmonary resuscitation secondary to pericarditis, primary lung cancer, and kidney failure with concomitant hyperkalemia.…”
Section: Risk Factorsmentioning
confidence: 99%